2017
DOI: 10.1111/1440-1630.12380
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and consequences of falls among older adult trauma patients: Considerations for injury prevention programs

Abstract: Results highlight differences among age groups of fallers admitted for trauma care and can help to inform injury prevention programs related to outdoor and indoor falls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
0
8
0
3
Order By: Relevance
“…There were 100 records that reported on the prevalence of AOD involvement in injury events. Of the 100 records that reported on all causes of injury (excluding transport events), 30 studies reported on the prevalence of AOD involvement in patients presenting to hospital after falls 24–52. One of these studies was excluded, since it reported exclusively on patients who denied consuming alcohol in the past year 38.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were 100 records that reported on the prevalence of AOD involvement in injury events. Of the 100 records that reported on all causes of injury (excluding transport events), 30 studies reported on the prevalence of AOD involvement in patients presenting to hospital after falls 24–52. One of these studies was excluded, since it reported exclusively on patients who denied consuming alcohol in the past year 38.…”
Section: Resultsmentioning
confidence: 99%
“…Studies were predominantly from the USA (13 studies) 24 26–28 31 36 39 41–44 48–52. There were two studies from Norway,25 29 30 46 and one each from Bhutan,35 Ghana,37 Spain,33 34 Taiwan,32 45 Tanzania45 and the UK 40.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Internationally, the number of older adults receiving care in emergency departments (EDs) has increased by more than 20% since 2001. 5 In Australia, approximately 17%-18% of ED presentations in older adults were because of falls and between 43% and 57% of these people were discharged directly home. 6,7 Various resources have been developed for staff working in EDs with older adults, including guidelines with fall prevention recommendations and core competencies (including fall-related skills).…”
Section: Introductionmentioning
confidence: 99%
“…Embora a maioria das quedas não resulte em lesões graves, em torno de 5% dos eventos causam fraturas ou hospitalizações (Ambrose, Cruz & Paul, 2015;Rubernstein, 2006), além disso, muitos idosos podem apresentar consequências psicossociais como sentimentos de medo e falta de confiança (Whipple, Haamel & Talley, 2017;Alves et al, 2017). Sendo assim, dependo da sua gravidade, um único evento pode colocar os idosos em risco de declínio funcional, institucionalização e, até mesmo, morte (Chippendale, Gentile & James, 2017;Antes, D'Orsi &Benedetti, 2013).…”
Section: Introductionunclassified